THE COSMOPOLITAN ASPECT OF YURI KUZNETSOV’S EARLY WORK - Maxim D. Ponomarenko (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The purpose of this article is to consider the cosmopolitan aspect of Yuri Kuznetsov’s early works. Kuznetsov was the Russian poet of the 2nd half of the 20th century. The main method of research for us is the method of ontological poetics, and elements of interdisciplinary and comparative analysis. It allows us to consider an artistic text in the context of consciousness and subconsciousness, archetypes and phenomena of the surrounding being. They, in turn, form a personal author’s myth. Yuri Kuznetsov creates his own poetic myth based on the real events of his own biography. In particular, the phenomenon of war has a key influence on it. The author is a “children of war” generation representative (born in 1941). His father died at the front in 1944. This fact determines Yuri Kuznetsov’s further outlook and path in literature. The article examines a number of the poet’s early poems. The opposition of Nature and War concepts can already be traced to each other at this stage. The latter is portrayed as an unnatural phenomenon that hinders the development of personality. Nature symbolizes life and natural dynamics, and War symbolizes halt and death, lack of dynamics. It comes into direct conflict with the laws of Nature. The leitmotif of the poet’s early work is the idea of man and nature’s unity. Such unity, in the end, allows us to build a progressive cosmopolitan model of the Home-Universe. It consists of three parts: Family-Home, Motherland-Home, and Planet-Home. The cosmopolitan orientation of Yuri Kuznetsov’s poems is manifested in his craving for the idea of “world citizenship”. At the same time, the fundamentally important fact is not the rejection of the Motherland and one’s own cultural identity, but their inclusion in a common threefold ontological model. The article also attempts to compare Yuri Kuznetsov’s work with the ideas of Russian symbolism representatives of the early 20th century. Conclusion. Based on the interdisciplinary analysis of the literary text, here are the following research results: 1. In poet Yuri Kuznetsov’s early works there is a process of upward movement along the vertical axis: from the personal myth and the lyrical “I/me” to the universal human experience. The latter, at the same time, is a unifying factor leading to the formation of an anti-war position. 2. The poet’s early works use cosmopolitan motives in the context of the verb “to create” which is semantically equivalent to the verbs “to generate” and “to build”, as well as connotatively close to the ontological processes of dynamics and movement. The verb “to create” is also opposed to the concept of War and is considered as part of the author`s anti-war position. Creativity acts both as an anti-destructive manifesto and as a means of uniting elements of the artistic world scattered by war. We should note that the author’s artistic world is closely connected with his biography and personal family history. 3. Through creativity Yuri Kuznetsov attempts to comprehend the phenomenon of War in three interdependent contexts: family, country and planet (“all people”). This approach allows us to come to the conclusion that war is incompatible with the natural course of things, that is, in fact, with the laws of Nature. 4. The sphere of the unconscious plays a key role in the formation of the author’s anti-war position and the stepped three-part model of the House. One more important connotation of the verb “to create” is connected with it. This connotation can be defined as the process of integrating the personal author’s unconscious into the collective unconscious (“great”). At the same time, a prerequisite for successful integration is a “storm”, a certain dynamic involving vertical ascent. The conclusions of such integration lead the author to the idea of “world citizenship” and universal interconnection. This, in turn, forms an anti-war position based on the similarity of the two sides in the “friend-foe” opposition.